Activation of peroxymonosulfate using drinking water treatment residuals modified by hydrothermal treatment for imidacloprid degradation. (September 2020) - Cui, Xiaoling; Liu, Xitao; Lin, Chunye; He, Mengchang; Ouyang, Wei
Abstract: In this study, water treatment residuals (WTRs), a safe and valuable by-product containing iron, was used as a precursor for preparing effective activator (HWTRs) of peroxymonosulfate (PMS) for imidacloprid (IMD) degradation by hydrothermal treatment. Several affecting parameters on IMD degradation including PMS concentration, HWTRs dosage, initial pH and water matrix were discussed. The results of degradation experiments demonstrated that within the reaction time of 4 h, 97.64% of IMD could be removed with 0.5 g L −1 HWTRs and 1.5 mM PMS, and the acidic conditions were favorable for IMD degradation. Both sulfate radicals (SO4 − ) and hydroxyl radicals (·OH) were generated to attack the target pollutant IMD, and ·OH was the dominating radical in the HWTRs/PMS system, which was confirmed by the results of radicals scavenging experiments, electron spin-resonance spectroscopy (ESR) tests and quantitative analysis. What's more, X-ray photoelectron (XPS) spectroscopy was used to further verify the activation mechanism. Consequently, the activation by Fe(II) on the surface of HWTRs might dominate the reaction was confirmed. In addition, the possible degradation pathways of IMD were proposed on the basis of the degradation intermediates identified by LC-MS. This study offers an innovative idea for modifying raw WTRs to prepare efficient catalysts to activate PMS under relatively mild conditions. Graphical abstract: Image 1 Highlights: WTRs was converted into an effective catalyst by hydrothermal treatment. The optimal catalyst preparation parameters were discussed. The prepared catalyst showed excellent performance as peroxymonosulfate activator. SO4 . − and ·OH were the main reactive species in the system. Degradation pathways of imidacloprid were proposed based on intermediates.